Diseño de un Sistema de Gestión de Inventarios para el Almacén Técnitaller S.A.S de la Cuidad Neiva-Huila (2021)
A deficient inventory management in the organization leads to the appearance of deviations such as loss of merchandise, obsolescence, lack of product availability, reprocesses, which affect the quality of service, financial statements and the management's own management. The present research work refers to the design of an inventory management system for the warehouse Técnitaller S.A. S of the city of Neiva-Huila; whose mission is the sale and maintenance of vehicles; according to the diagnosis made problems such as those mentioned above affect the service of the company; the current system is of empirical character generating over costs associated with the maintenance of inventory, cost of ordering, shortages, among others: as a result of this analysis a model of inventory management was proposed from a software (Office Word), which consists of 4 modules (purchasing, warehouse, inventory and dispatch) and has an implementation cost of $ 16. The advantages of this proposal are that it will optimize costs by the factors mentioned above, it proposes a new order for its administration based on the ABC system, it ensures the replenishment processes and the management of marking, inputs and outputs of the merchandise.